Meningkatkan Kemampuan Mengenal Konsep Ruang Dengan Bermain Drum Untuk Anak Tunagrahita Ringan - Agus - Wahyu (Universitas Negeri Padang, 2014)
Mental retardation children experienced disturbances in the Desert about SLB Limas spaces left-right.This research uses a Single Subject Research (SSR) and design A, B. Research Subject is a mild mental retardation. The Target behaviour from this research is the ability of children to determine the concept of left-right space as measured by calculating the percentage. Research results are analyzed include the number of observations on the baseline conditions as much as five times the meeting and conditions of intervention as much as ten times.After the data analyzed were obtained the following results in the baseline phase that the child was only able to recognize the concept of space above ground. On a phase of intervention, namely conducting lessons with use drumming, children can get to know the concept of space is left-right (value reaches 100%).